Relationship between gut microbiota and osteoarthritis: a scientometric analysis - He, Zhicheng; Xu, Songrui; Ma, Ningning; Zuo, Yin; Chen, Xinyu; Yan, Ting; Li, Pengcui; Pan, Yongchun; Wei, Xiaochun; Tian, Zhi (Frontiers in Microbiology, 2025)
ObjectiveThis study aims to visualize and analyze the literature on osteoarthritis (OA) and gut microbiota (GM) over the past decade (2011–2024) using bibliometric methods, and to understand the current research status and development trend in this field.MethodsWeb of Science Core Collection was used as the source of literature, and the time limit was from January 2011 to July 2024, and the topics included “osteoarthritis” and “gut microbiota.” The included literature was analyzed in terms of annual distribution, country distribution, institutions, authors, keywords, and journals using Excel and CiteSpace.ResultsA total of 192 articles were identified. Despite the limited volume, publication output demonstrated a consistent growth trend over the study period. Countries and institutions with the highest publication output and citation impact were predominantly located in China and the United States. The journals with the highest number of articles were mostly concentrated in Switzerland, and the research direction was mainly related to osteoarthritis and cartilage. The keywords appearing in the searched articles were gut microbiota, knee osteoarthritis, inflammation, rheumatoid arthritis, and gut microbiome.ConclusionThe research on OA and GM in China and abroad has shown an increasing trend, and the content of the research has been deepening with the passage of time. While the precise mechanisms remain elusive, targeting GM modulation emerges as a promising therapeutic strategy for OA, with potential clinical applications in disease prevention and management.